Case report: Pulmonary non-Langerhans cell histiocytosis in a dog with acute interstitial granulomatous pneumonia - Granger, Kyle L.; Williams, Kurt; Ohlendorf, Alex; Shropshire, Sarah; Hall, Kelly E. (Frontiers in Veterinary Science, 2025)
BackgroundPulmonary involvement of Non-Langerhans Cell Histiocytosis (PNLCH) is a rare cause of interstitial pulmonary disease in people and are classified as either Erdheim-Chester disease (ECD) or Rosai-Dorfman disease (RDD). In veterinary medicine, feline pulmonary Langerhans cell histiocytosis (PLCH) has been identified as an infiltrative histiocytic disorder with an insidious onset of progressive respiratory distress and is non-responsiveness to empiric therapies. Unfortunately, subsequent death either from respiratory failure or humane euthanasia are the reported outcomes in all reported cases. To date, a similar primarily pulmonary histiocytic disease has not been described in dogs. We present a case of an 8-year-old male intact Rottweiler with acute, progressive respiratory failure with a post-mortem diagnosis of PNLCH.Case summaryAn 8-year-old male intact Rottweiler presented following approximately 2 weeks of lethargy, anorexia, hypersalivation, and progressive respiratory distress characterized by intermittent wheezing, increasing inspiratory and expiratory effort, and tachypnea. Diagnostic imaging demonstrated a multifocal cranioventral alveolar pattern with nodules in the lung periphery. There were no significant changes appreciated in bloodwork. Despite empiric antimicrobials, oxygen support, and other supportive care measures, the patient continued to deteriorate and was subsequently euthanized. Post-mortem analysis was confirmatory for single-organ PNLCH.New or unique information providedThis case report represents the first reported case of canine PNLCH. Additionally, this report also provides further characterization of PNLCH in dogs with ante-mortem diagnostic imaging, cytologic evaluation of lung tissue, and post-mortem immunohistochemical characterization of canine PNLCH.